Technological applicability of mama-cadela (Brosimium gaudichaudii Trecúl) seed fl our in gingerbread - Maria Alves, Vânia (2021)
The objective of this paper was the partial addition of mama-cadela seed flour in the production of gingerbreadwith chocolate coating for a partial substitution of wheat flour (15 percent and 25 percent relative to flour), in order to verifyits contributions to the chemical, physical properties of the product developed. After the analyses, again observed that themama-cadela seed flour had an improvement regarding a few chemical parameters, such as an increase; in the amount of ashesin the gingerbread with chocolate coating with 15 percent mama-cadela seed flour and 25 percent mama-cadela seed flour,respectively (1.20 percent, 1.37 percent); the gingerbread with 25 percent of mama-cadela seed flour showed lower wateractivity, favoring the product life; texture proved softer and more pleasant for the gingerbread with coating. Therefore, weconclude that the substitution of wheat flour with mama-cadela seed flour it is a viable and nutritious option, not only preventsseed waste, but has a positive effect on the physical, chemical characteristics of the gingerbread.